Red Pope A Biography of Cardinal Willem van Rossum C.Ss.R. (1854-1932) - Poels, Vefie (Radboud University Press, 2023)
Arriving in Rome from the Netherlands in 1895, the Catholic priest and Redemptorist Willem van Rossum (1854-1932) rose quickly through the ranks of the curia. In many ways an outsider, he made a resounding success of his career. His zeal in the fight against the 'virus of modernism' earned him a cardinal's hat in 1911, and he was appointed prefect of the Congregation of Propaganda Fide in 1918. As 'red pope' or head of the Vatican's mission department, Van Rossum led a hard-fought and ultimately successful campaign to separate missionary policy, fundraising and staffing from Western nationalism, and concentrate control over the worldwide missionary project at supranational level in Rome. He was the driving force behind two programmatic documents on the missions by Popes Benedict XV and Pius XI, which promoted the building up of indigenous churches and the educating of native clergy, thus helping to create a favourable position for the Catholic church during the subsequent wave of decolonisation. In the meantime, Van Rossum continued to decry Italian dominance in the church as well as the curia's inefficiencies, for instance in a vituperative pamphlet that he wrote shortly before his death. This scholarly biography of Willem van Rossum rescues this great strategist behind the 'popes of the missions' from oblivion, and throws fascinating light on the history of the Catholic church and the Roman curia from the late nineteenth century until far into the twentieth.